Analisis Penggunaan Bahasa Dalam Interaksi Jual Beli Di Pajak MMTC Medan - Delfira Almuharomah Lubis; Ledy Novwanty Nainggolan; Irfansyah Barus; Wijar Pakpahan; Muharina Harahap (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study aims to analyze language use in buying and selling interactions at the Medan MMTC Tax Office, focusing on the language used, factors influencing language choice, and the function of language in the transaction process. The study employed a qualitative approach with descriptive methods. Data were obtained through observation, interviews, and documentation, involving sellers and buyers as the primary data sources. The results indicate that Indonesian is the most dominant language used in buying and selling interactions because it serves as an effective means of communication amidst the diverse ethnicities and linguistic backgrounds of the community. Furthermore, code-switching and code-mixing phenomena involving the use of regional languages, such as Batak and Javanese, were also found, primarily to foster social closeness between sellers and buyers. Language choice is influenced by several factors, including ethnic background, level of social closeness, age, and the communication situation. Language in buying and selling transactions serves not only as a means of conveying information about goods and prices, but also as a means of building social relationships, creating comfort, and facilitating negotiation. The findings of this study indicate that Indonesian continues to play a crucial role as a connecting language in the economic activities of multicultural communities, while regional languages serve as complementary tools that strengthen interpersonal relationships in buying and selling interactions.